2009
DOI: 10.21273/hortsci.44.6.1581
|View full text |Cite
|
Sign up to set email alerts
|

High Tunnel versus Open Field: Management of Primocane-fruiting Blackberry Using Pruning and Tipping to Increase Yield and Extend the Fruiting Season

Abstract: Primocane-fruiting blackberries (Rubus subgenus Rubus Watson) may offer opportunities for season extension and off-season fruit production, particularly in mild climates with protected culture. In May 2005, plants of ‘Prime-Jan’® were established at the Oregon State University–North Willamette Research and Extension Center, Aurora, OR. Half of the planting was established under a high tunnel and the remainder planted in an adjacent open field. In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…Soft-tipping the primocane of annual blackberries at 1 m induced branching and increased flower and fruit number and yield three-fold without affecting fruiting season . A double-tip, where branches are further shortened, has been shown to increase yield (Thompson et al, 2009). Genotype, rate of flowering, and climate may affect best pruning methods (Strik, personal observation).…”
Section: Erectmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft-tipping the primocane of annual blackberries at 1 m induced branching and increased flower and fruit number and yield three-fold without affecting fruiting season . A double-tip, where branches are further shortened, has been shown to increase yield (Thompson et al, 2009). Genotype, rate of flowering, and climate may affect best pruning methods (Strik, personal observation).…”
Section: Erectmentioning
confidence: 99%
“…Use of spunbound row covers from late winter, before primocane emergence, through ~0.6 m primocane height advanced flowering and fruiting by two weeks in Oregon , but had no impact in North Carolina, USA (Fernandez and Ballington, 2010). In plants where primocanes were mowed back to ground level when height averaged ~0.5 m, fruit production was delayed by about four weeks (Thompson et al, 2009). Producing primocane-fruiting blackberry in an un-heated tunnel extended the harvest season about three weeks in Oregon's temperate climate (Thompson et al, 2009).…”
Section: Erectmentioning
confidence: 99%
See 1 more Smart Citation
“…The hard-hedging treatments may have performed better if they had been done earlier or at the same time as the soft-hedging treatments; this would only have been possible if canes had been cut back (hedged) to a shorter height than 1 m on week 1. Thompson et al (2009) found that canes tipped as short at 0.5 m produced high yield. It is also possible that when plots were hedged, some canes were tipped that had already produced flower buds; this would have led to a reduction in yield/plot (Drake and Clark, 2003;B.C.…”
Section: Resultsmentioning
confidence: 96%
“…S oft-tipping (removal of 2-5 cm) primocane-blackberry canes once (Drake and Clark, 2003;Strik et al, 2008 andThompson et al, 2009) or double-tipping (main cane and branches; Thompson et al, 2009) has been shown to increase yield compared with untipped canes and has become standard industry practice (B.C. Strik, personal observation).…”
mentioning
confidence: 99%